# How do I solve for t?

1/ 3 square root 2 = 1/ t-2

### 1 Answer

Relevance

- Anonymous8 years agoFavorite Answer
1/3 √2 = 1 / t - 2

Multiply both sides of the equation by t - 2, so that t isn't in the denominator.

1/3 √2 (t - 2) = 1

^there's no t - 2 on the right side of the equation because multiplying by t - 2 cancelled out the t - 2 in the denominator.

Now, subtract 1/3 √2 from each side:

t - 2 = 1 - 1/3 √2

Finally, add 2 to each side so t is by itself, and then collect like terms on the left side of the equation:

t = 1 + 2 - 1/3 √2

t = 3 - 1/3 √2

- Login to reply the answers

Still have questions? Get your answers by asking now.